Propagating plants how to create new plants for free - Toogood, Alan R.; Anderson, Peter 1956 July 20-
How long do your seedlings need to germinate? What makes a healthy stem cutting? How do you know what type of rootstock to use when grafting plants? Find all the answers within, alongside more than 1,800 detailed illustrations and photos to refer to, plus the experts' secrets to perfect plant propagation. Ideal for the thrifty gardener who wants plants for free, or who wants to gift favorite plant cuttings to friends and family; and useful for budding house plant owners with an interest in propagating succulents and other house plants. Fill your garden with beautiful plants for next-to-nothing with this brand new edition of the most comprehensive guide to propagating plants ever published.